Open Bibliographical Data Workflows and the Multilinguality Challenge - Vojtěch Malínek; Tomasz Umerle; Edward Gray; Ivan Heibi; Péter Király; Christiane Klaes; Przemysław Korytkowski; David Lindemann; Arianna Moretti; Charlotte Panušková; Róbert Péter; Mikko Tolonen; et al. (Journal of Open Humanities Data)
The aim of the paper is to present and analyze workflows for bibliographical data curation and research that were created during the ‘Open Bibliodata Workflows’ project realised by the Bibliographical Data Working Group from the DARIAH ERIC consortium. These workflows are available via SSH Open Marketplace. Its role in the SSH infrastructural system is subsequently shortly introduced. Bibliodata-related workflows are needed at different levels of data creation and research, both for specific software features or data sources as well as for consolidating methodological aspects of bibliographical data curation. Set of five workflows showcasing various models of bibliodata related workflows is discussed afterwards. First of these workflows, From Library Data to Research Data describes conversion of library data into a dataset for data-based research. The other four are centred around leveraging existing tools and services. AVOBMAT: how to analyze and visualize bibliographical data and texts showcases a tool for combining text analysis and metadata-based research. Metadata crosswalk for citation data production in OpenCitations is a step-by-step instruction for using the OpenCitations infrastructure, a state-of-the-art service for sharing open citation data. LODification of bibliographical data: Zotero to Wikibase migration illustrates current dynamic developments concerning metadata in the field of Linked Open Data. Finally, the National Information Processing Institute from Poland (OPI PIB) prepared a workflow Studies on science and higher education system in Poland using the RAD-on platform, discussing how to use their dataset for research. Analysis of these workflows reveals particular needs to address the multilinguality challenge in the bibliodata field. On the level of curation this challenge is met with application of international standards for bibliographical data processing that on many occasions do not prioritise harmonization of multilingual datasets. The main curatorial techniques on how to solve multilingual issues in bibliographical data are briefly outlined. When we are tackling research questions the multilinguality challenge is even more prominent. Hence we are closing this article with a proposal for a preliminary workflow for processing multilingual bibliodata.